Eenheid en gelykheid uitgedruk deur die metafoor van die wapenrusting in Efesiers 6:10-18 - Alta Vrey (In die Skriflig, 2022)
The Holy Spirit and the Word of God are gifts to the whole church. Every believer in Jesus Christ is part of the body of Christ, the temple of God, the household of the Father and the army of the Spirit. One of the main themes of the letter to the Ephesians is unification in Christ between Jews and Gentiles. The author concludes his letter in Ephesians 6:10 with the metaphor of the armour of God: ‘In conclusion, be strong in the Lord [be empowered through your union with Him] and in the power of His might.’ (AMP). Our union with Christ, which should be reflected in our union with other believers, empower us to be strong in our fight against evil in this world.